2020
DOI: 10.1021/acsami.0c05406
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic/Hydrophobic Heterogeneity Anti-Biofouling Hydrogels with Well-Regulated Rehydration

Abstract: Hydrogels, as a representative of soft and biocompatible materials, have been widely used in biosensors, biomedical devices, soft robotics, and the marine industry. However, the ir-recoverability of hydrogels after dehydration, which causes the loss of original mechanical, optical, and wetting properties, has severely restricted their practical applications. At present, this critical challenge of maintaining hydrogels’ accurate character has attracted less attention. To address this, here we report a hydrogel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 32 publications
0
35
0
1
Order By: Relevance
“…To verify the introduction of Ni-catchers, we compared the pristine NiTi, H-NiTi, and CS-NiTi from surface morphology, WCAs, XPS spectra, transmittance, optical images, and biocompatibility. As shown in Figure 2A , the introduction of Ni-catchers resulted in the porous morphology of CS-NiTi, compared with the flat morphology of H-NiTi, probably because of the phase separation ( Su et al, 2020 ). Furthermore, the WCAs decreased from 83.5 ± 3.7° (NiTi) to 59.0 ± 3.4° (CS-NiTi), indicating the hydrophilicity of CS-NiTi ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…To verify the introduction of Ni-catchers, we compared the pristine NiTi, H-NiTi, and CS-NiTi from surface morphology, WCAs, XPS spectra, transmittance, optical images, and biocompatibility. As shown in Figure 2A , the introduction of Ni-catchers resulted in the porous morphology of CS-NiTi, compared with the flat morphology of H-NiTi, probably because of the phase separation ( Su et al, 2020 ). Furthermore, the WCAs decreased from 83.5 ± 3.7° (NiTi) to 59.0 ± 3.4° (CS-NiTi), indicating the hydrophilicity of CS-NiTi ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 98%
“…The CS-NiTi was fabricated according to previous literature, with some modifications ( Su et al, 2020 ). Firstly, pristine NiTi alloy was immersed in bis-HEMAP (5% ethanol solution) for 24 h and washed with deionized water for three times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The swelling or deswelling behaviors occurring in these processes would depend on the swelling ratio of the hydrogel and can also cause feature deformation. 70 As is introduced above, hydrogel-induced swelling behavior can even be employed as a specific patterning method. The swelling behavior utilized in these methods will be controllable and precisely designed.…”
Section: Techniques To Fabricate Patterned Hydrogelsmentioning
confidence: 99%
“…With the increasing attention to healthcare, the practical values of wettability materials in biomedical‐related fields are receiving remarkable interests and researches. [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] Previous literatures have revealed that surface wettability, especially the superwettability like superhydrophobicity and superhydrophilicity, have great influence on the biomolecular behaviors such as adhesion and proliferation. [ 32 , 33 , 34 ] To be specific, the superhydrophobic surfaces are capable of effectively resisting bacterial adhesion, protein adsorption, cell adhesion, and blood coagulation; while the superhydrophilic ones have the ability of antibacterial and facilitating cell attachment.…”
Section: Introductionmentioning
confidence: 99%